Genetic markers in renal adenocarcinoma - Germenis, A.; Dimopoulos, M.A.; Fertakis, A.; Dimopoulos, C. (Journal of Urology, 1984)
The distribution of phenotypes and gene frequencies of the 3rd component of complement (C3), group-specific component (G(c)), haptoglobin (Hp) and transferrin (T(f)) were studied in 50 patients with renal adenocarcinoma. The statistical analysis of our findings in comparison to the frequency of these genes in the general population does not reveal any correlation between the distribution of the Hp and Tf phenotypes and the disease. On the contrary, a statistically significant association was found between renal adenocarcinoma and C3(F) and Gc 2 genes. The relative risk incidence of this malignancy is 2.07 and 1.94 respectively for the carriers of these genes. These data indicate that genetic factors, possibly related to the immune mechanisms and calcium metabolism, play a role in the pathogenesis of renal adenocarcinoma.